Why the elderly appear to be more severely affected by COVID-19: The potential role of immunosenescence and CMV - Kadambari, S; Klenerman, P; Pollard, AJ (Wiley, 2020)
The significantly higher mortality rates seen in the elderly compared with young children during the coronavirus disease 2019 (Covid‐19) pandemic is likely to be driven in part by an impaired immune response in older individuals. Cytomegalovirus (CMV) seroprevalence approaches 80% in the elderly. CMV has been shown to accelerate immune ageing by affecting peripheral blood T cell phenotypes and increasing inflammatory mediated cytokines such as IL‐6. The elderly with pre‐existing but clinically silent CMV infection may therefore be particularly susceptible to severe Covid‐19 disease and succumb to a cytokine storm which may have been promoted by CMV. Here, we evaluate the potential role of CMV in those with severe Covid‐19 disease and consider how this relationship can be investigated in current research studies.